Removal of 4-nitrophenol from aqueous solution by natural low-cost adsorbents - Varank, Gamze; Demir, Ahmet; Yetilmezsoy, Kaan; Top, Selin; Sekman, Elif; Bilgili, M. Sinan (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2012)
Use of adsorption isotherms, kinetics and thermodynamics for the removal of 4-nitrophenol (4-NP) from aqueous solutions by zeolite and bentonite has been investigated in a lab-scale batch study. Various parameters, such as adsorbent dosage, initial concentration of 4-NP; pH, operating temperature, and agitation time have been optimised for the maximum removal of 4-NP. With the optimized conditions (180 rpm agitation rate, 240 min agitation time, 7 pH, 298 K, 100 mg/L initial adsorbate concentration, and 5 g/L & 20 g/L for zeolite & bentonite dosages respectively), the removal percentages of 4-NP for natural zeolite and bentonite are found to be 51% and 68% respectively. The adsorption mechanisms and characteristic parameters for the present process are analyzed by four two-parameter (Langmuir, Freundlich, Temkin and Dubinin-Radushkevich), five three-parameter (Redlich-Peterson, Toth, Sips, Radke-Prausnitz and Khan) isotherm models, and six kinetic models (Lagergren's pseudo-first order, Ho and McKay's pseudo-second order, Elovich, intraparticle diffusion, Bangham and modified Freundlich) using the non-linear regression methodology. Among the two-parameter isotherms, the experimental data yield excellent fits with Langmuir and Freundlich isotherm equations for both adsorbents. Three-parameter isotherms show higher determination coefficients (R-2 > 0.999) and lower residual and standard errors than two-parameter isotherms. Of the three-parameter isotherms, Toth and Khan isotherms are the best to describe the experimental data of the 4-NP-zeolite system. Results of the kinetic studies show that the best-fitted kinetic models are the modified Freundlich, the Elovich and the Ho and McKay's pseudo-second order for both 4-NP-zeolite and 4-NP-bentonite systems. The results also indicate that three-parameter isotherms have no significant correlations for the 4-NP-bentonite system. Adsorption thermodynamics of 4-NP [equilibrium constant, standard free energy changes, standard enthalpy and entropy changes] on zeolite and bentonite are also studied at various temperatures of 298, 318 and 338 K. The values of enthalpy changes and entropy changes are found to be -4.43 and -7.77 kJ/mol, and 3.43 and -9.76 kJ/mol.K for zeolite and bentonite respectively. The thermodynamic analysis indicates that the present adsorption systems are found to be exothermic, and the adsorption of 4-NP on zeolite and bentonite is spontaneous and physical in nature. Findings of this study clearly show that these materials could be used as efficient adsorbents for the removal of 4-NP from aqueous solutions.
Keywords: 4-Nitrophenol; Adsorption; Bentonite; Isotherm; Kinetic; Thermodynamic; Zeolite; BAGASSE FLY-ASH; ACTIVATED CARBON; WASTE-WATER; PHENOLIC-COMPOUNDS; HAZARDOUS DYE; BOTTOM ASH; CONGO RED; EQUILIBRIUM; KINETICS; Chemistry; Engineering